Eficiência da seleção per se, em híbridos simples e indireta para resistência a doenças no milho - Camargos, Renato Barbosa (2016)
The diseases in corn correspond to one of the main limiting factors to continue obtaining gains in productivity, in this cereal breeding programs. With this, a wide discussion has been held about strategies that can provide greater efficiency during the selection process. Faced with this, two distinct works were conducted, aiming to offer contributions that may guide future breeding works. The objectives of the first work were to study the genetic control and the selection efficiency based on the lineages per se’s behavior and based on the hybrids behavior, as the reaction to white spot, common rust and ear rot, in corn breeding programs, as well as the relation between the performance per se‟s of the lineages and of simple hybrids for the resistance to these diseases. For this, the behavior of 106 lineages and 661 hybrids in different locations in Brazil was evaluated for the reaction to these diseases. Subsequently, the relative importance of the additive and non-additive genetic effects on the expression of these characters was estimated, the association among the parameters considered when the selection was made in those generations and the gain with the selection. The results indicated that there is a predominance of additive effects for resistance to white spot and ear rot, whereas for common rust predicts effects of dominance. However, the hybrids evaluation by means diallel analysis was efficient in selecting for resistance to these diseases. The diseases and generations evaluated are interrelated, the increase in the resistance level has a more expressive correlated response when the selection is oriented by the reaction to the white spot and there is greater genetic similarity among the parameters considered in the selection oriented by the hybrids behavior. In the second work, the objective was to study the efficiency of indirect selection for resistance to white spot, cercosporiosis, helmintosporiosis and ear rot, by means productivity evaluation using biplots. Thus, the behavior of 242 lineages was evaluated for these diseases, in two sites, in Minas Gerais state. After that, the mixed models approach associated to multivariate techniques was used to study the relation among productivity, foliar diseases and ear diseases. It was concluded that the husked ears yield has a higher degree of association with ear rot than with the foliar diseases evaluated, which justifies the indirect selection for resistance to ear rot by means productivity evaluation.